Gene expression analysis of ischaemia and reperfusion in human microsurgical free muscle tissue transfer. - Dragu, Adrian; Schnuerer, Stefan; Surmann-Schmitt, Cordula; von der Mark, Klaus; Stürzl, Michael; Unglaub, Frank; Wolf, Maya B.; Leffler, Mareike; Beier, Justus; Kneser, Ulrich; Horch, Raymund E. (Journal of Cellular and Molecular Medicine, 2011)
The aim of this study was to analyse various gene expression profiles of muscle tissue during normoxia, ischaemia and after reperfusion in human muscle free flaps, to gain an understanding of the occurring regulatory, inflammatory and apoptotic processes on a cellular and molecular basis. Eleven Caucasian patients with soft tissue defects needing coverage with microsurgical free muscle flaps were included in this study. In all patients, the muscle samples were taken from free myocutaneous flaps. The first sample was taken before induction of ischaemia in normoxia (I), another one after ischaemia (II), and the last one was taken after reperfusion (III). The samples were analysed using DNA-microarray, real-time-quantitative-PCR and immunohistochemistry. DNA-microarray analysis detected multiple, differentially regulated genes when comparing the different groups (I-III) with statistical significance. Comparing ischaemia (II) versus normoxia (I) educed 13 genes and comparing reperfusion (III) versus ischaemia (II) educed 19 genes. The comparison of reperfusion (III) versus normoxia (I) yielded 100 differentially regulated genes. Real-time-quantitative-PCR confirmed the results of the DNA-microarrays for a subset of four genes (CASP8, IL8, PLAUR and S100A8). This study shows that ischaemia and reperfusion induces alterations on the gene expression level in human muscle free flaps. Data may suggest that the four genes CASP8, IL8, PLAUR and S100A8 are of great importance in this context. We could not confirm the DNA-microarry and real-time-quantitative-PCR results on the protein level. Finally, these findings correspond with the surgeon's clinical experience that the accepted times of ischaemia, generally up to 90 min., are not sufficient to induce pathophysiological processes, which can ultimately lead to flap loss. When inflammatory and apoptotic proteins are expressed at high levels, flap damage might occur and flap loss is likely. The sole expression on mRNA level might explain why flap loss is unlikely.